Uzbekistan - Living Standards Assessment : Policies to Improve Living Standards, Volume 1. Summary Report - World Bank (Washington, DC, 2013)
Since independence, Uzbekistan has followed a distinct economic strategy, entailing gradual transformation of the economy, while emphasizing social stability. The "Uzbek Model" of development has focused on developing industrial and manufacturing capacity in a predominantly agricultural economy, using direct and substantial state guidance. An important objective of the strategy has been to raise living standards and expand employment opportunities, while protecting vulnerable groups against abject poverty. Has this approach alleviated the problems of poverty inherited by the country? This report provides the first national level picture of living standards in Uzbekistan since independence. It has three main goals: (i) to examine the current status of living standards in Uzbekistan (ii) to identify key challenges and constraints to improving living standards, and (iii) to suggest priority policy actions that are needed for broad based improvements in living standards in the country. The report was prepared in close collaboration with a working group from the Government of Uzbekistan, to ensure the relevance of the findings and to build capacity for analytical evaluation of living standards using household survey data. The report is based on the recently improved and nationally representative Family Budget Survey (FBS) (2000/01) carried out by the Uzbek statistical authorities. Since 2000/01 was the first year of implementation of the revised nationally representative survey, the new survey is considered by the Statistical Authorities to be a pilot. This is also the first time the data have been used for poverty analysis, and the exercise has yielded important feedback for further strengthening the survey. Despite these important caveats, the FBS does provide the first comprehensive information on living standards in the country, and represents the best available information at this time. Results that appear to contradict conventional wisdom cannot be rejected a priori, since they represent the responses of about 10,000 households. They must be verified with future rounds of the survey as well as special studies. In addition to the FBS, the report uses other sources of information, including surveys of firms, farms, institutions and individuals, as well as administrative data. The study also uses international evidence to compare and contrast Uzbekistan's living standards and policy outcomes relative to other countries, including CEE (Central and Eastern European) countries and other CIS (Commonwealth of Independent States) countries. This report comprises two volumes. This first volume provides a summary of the findings and key policy recommendations of the report, preceded first by a brief overview of the key messages. The second volume contains the more detailed technical analysis on which this first volume is based.